The Curricular Reform and Implementation Barriers for Islamic Religious Education Teachers in Indonesia's Merdeka Belajar Era - Richway; Maftuhah; Riyadi, Dedi Eko; Khozin; Humaidi, M. Nurul (Universitas Muhammadiyah Malang, 2025)
This study investigates the obstacles encountered by Islamic Education (PAI) instructors in implementing the Merdeka Belajar Curriculum and the tactics utilized to overcome these difficulties. The Merdeka Curriculum represents a significant reform in Indonesia's educational system, prioritizing differentiated learning, learner autonomy, and flexible instructional design, necessitating that educators modify their pedagogical approaches to accommodate students' varied skills and needs. Nonetheless, its execution in Islamic Education poses unique obstacles. Data were gathered using a qualitative descriptive methodology through in-depth interviews, classroom observations, and document analysis with PAI teachers at the junior secondary level. The findings identify several significant obstacles, including inadequate conceptual comprehension of the curriculum framework, insufficient professional development and socialization, challenges in creating differentiated learning materials, ambiguous operational guidelines, weak institutional support, and limited leadership engagement. These obstacles impede instructors' pedagogical preparedness and diminish the efficacy of curriculum execution in classroom practice. In response, educators have implemented many coping mechanisms, including peer cooperation, self-directed learning, and informal instructional modifications. Nonetheless, these endeavors continue to be disjointed and predominantly solitary in character. This study highlights the critical necessity for systematic and ongoing professional development, robust instructional leadership, and cohesive policy support to improve teachers' ability to effectively execute the Merdeka Belajar Curriculum in Islamic Religious Education. The results enhance overarching dialogues regarding curriculum reform and educator preparedness within faith-based educational settings.